Relaxation of the 2a1 ionized water dimer: an interplay of intermolecular Coulombic decay (ICD) and proton transfer processes - Kumar, Ravi; Ghosh, Aryya; Vaval, Nayana (Journal of Chemical Physics, 2024)
This article investigates the relaxation dynamics of the ionized 2a(1) state of a water molecule within a water dimer. The study was motivated by findings from two previous pieces of research that focused on the relaxation behaviors of the inner-valence ionized water dimer. The present study discloses an observation indicating that water dimers display specific fragmentation patterns following inner-valence ionization, depending on the position of the vacancy. Vacancies were created in the 2a(1) state of the proton-donating water molecule (PDWM) and proton-accepting water molecule (PAWM). Utilizing Born-Oppenheimer molecular dynamics simulations, the propagation of the 2a(1) ionized state was carried out for both scenarios. The results revealed proton transfer occurred when the vacancy resided in the PDWM, accompanied by the closing of decay channels for O-H bond distance (RO-H) > 1.187 & Aring; (matching Richter et al.'s findings). Conversely, when vacancy was on PAWM, we observed no closing of decay channels (aligning with Jahnke et al.'s findings). This difference translates to distinct fragmentation pathways. In PDWM cases, 2a(1) state ionization leads to H3O+ -OH center dot formation. In contrast, PAWM vacancies result in decay pathways leading to H2O+-H(2)O(+ )products.